Current electrocardiographic criteria for diagnosis of Brugada pattern: a consensus report - Bayés de Luna, Antoni; Borggrefe, Martin (Journal of electrocardiology, 2012)
Brugada syndrome is an inherited heart disease without structural abnormalities that is thought to arise as a result of accelerated inactivation of Na channels and predominance of transient outward K current (Ito) to generate a voltage gradient in the right ventricular layers. This gradient triggers ventricular tachycardia/ventricular fibrillation possibly through a phase 2 reentrant mechanism. The Brugada electrocardiographic (ECG) pattern, which can be dynamic and is sometimes concealed, being only recorded in upper precordial leads, is the hallmark of Brugada syndrome. Because of limitations of previous consensus documents describing the Brugada ECG pattern, especially in relation to the differences between types 2 and 3, a new consensus report to establish a set of new ECG criteria with higher accuracy has been considered necessary. In the new ECG criteria, only 2 ECG patterns are considered: pattern 1 identical to classic type 1 of other consensus (coved pattern) and pattern 2 that joins patterns 2 and 3 of previous consensus (saddle-back pattern). This consensus document describes the most important characteristics of 2 patterns and also the key points of differential diagnosis with different conditions that lead to Brugada-like pattern in the right precordial leads, especially right bundle-branch block, athletes, pectus excavatum, and arrhythmogenic right ventricular dysplasia/cardiomyopathy. Also discussed is the concept of Brugada phenocopies that are ECG patterns characteristic of Brugada pattern that may appear and disappear in relation with multiple causes but are not related with Brugada syndrome.